Remembering James Moffett: An Interview and Dialogue with Sondra Perl - Sheridan Blau; Sondra Perl (Journal of the Assembly for Expanded Perspectives on Learning, 2024)
Teachers reading these descriptions of Moffett’s teaching are likely to find in them models they too will be inspired to adapt for use in their own writing classrooms, wherever they teach.
Keywords: JAEPL Moffett